Photocurrent enhancement from diketopyrrolopyrrole polymer solar cells through alkyl-chain branching point manipulation. - Meager,I; Ashraf,RS; Mollinger,S; Schroeder,BC; Bronstein,H; Beatrup,D; Vezie,MS; Kirchartz,T; Salleo,A; Nelson,J; McCulloch,I (J Am Chem Soc, 2013)
Systematically moving the alkyl-chain branching position away from the polymer backbone afforded two new thieno[3,2-b]thiophene-diketopyrrolopyrrole (DPPTT-T) polymers. When used as donor materials in polymer:fullerene solar cells, efficiencies exceeding 7% were achieved without the use of processing additives. The effect of the position of the alkyl-chain branching point on the thin-film morphology was investigated using X-ray scattering techniques and the effects on the photovoltaic and charge-transport properties were also studied. For both solar cell and transistor devices, moving the branching point further from the backbone was beneficial. This is the first time that this effect has been shown to improve solar cell performance. Strong evidence is presented for changes in microstructure across the series, which is most likely the cause for the photocurrent enhancement.